Prototipe Alat Pemantau Kualitas Udara Pada Unit Pengujian Kendaraan Bermotor - Wardani, Ririswari Widya; Mukhtar, Agus; Burhanuddin, Aan (CV. IRA PUBLISHING, 2025)
This study aims to design and evaluate the performance of a prototype air quality monitoring device integrated with an exhaust fan in a vehicle testing room. The experimental method was employed to examine the relationship between variables. The increasing number of motor vehicles has an impact on air quality, particularly in emission testing areas. The device utilizes an MQ-7 sensor for gas detection and a DHT22 sensor for temperature and humidity, with data displayed in real time on an LCD screen. When the gas concentration exceeds nine ppm, the system activates an audible alarm and automatically turns on the exhaust fan to maintain air circulation. The exhaust fan expels hot air from the room while bringing in cooler outside air. Test results indicate that the device operates stably and provides accurate data, making it suitable as an air quality monitoring system in motor vehicle testing facilities.